RELATIONSHIP BETWEEN LENGTH AND WEIGHT AND CONDITION FACTORS OF SCAD FISH (Decapterus Russelli) CATCH OF PURSE SEINE IN LAMPUNG BAY AT KM.GUNUNG JATI - Setiawan, Ari; Basith, Abdul; Mualim, Rahmat; Setya, Dona (Politeknik Kelautan dan Perikanan Dumai, 2024)
The rate of exploitation of scads fish has increased, giving rise to concerns that the recruitment process is overfished. Relationship between length and weight in fisheries is one of the complementary information that needs to be known in relation to fisheries resource management. The purpose of this practice are to know the composition of yield, growth pattern catch of fly fish (Decapterus russeli) in the Lampung Bay. Sampling by simple random method were conducted in December until mid-March 2020. Samples consisted of catches from Lampung bay ships landed at the Lempasing fishing port. Data analysis by Linear Allometric Models (LAM), relative condition factors and fultons. The results showed the fly fish (Decapterus russeli) had a negative allometric growth pattern in December with a value of b = 2,7244, January with a value of b = 2,7153, February with a value of b = 2,8918, and in March with a value of b = 2,7067 value of 100,82-101,16 from relatively high relative condition factor and value of 2,85-2,91 from fulton condition factor which supports abundant feed which supports the life of Deccapterus russeli fish in good condition.